Você está na página 1de 3

# Conversion of capacitance from

f *pf
To

We know
0.1 f= x10-6 f
We need to convert 0.1 f capacitor to 0.1pf
Means x10-12 which is equal to pf
So we multiply with 10-6 & 10+6
Hence
0.1f=x10-6 x10-6x10+6f -------[10-6-6=10-12pf]
0.1f=x10+6pf
0.1f=x10+6pf
0.1f=x10+4pf
0.1f=capacitor code)
Hence in general form:

+6

af=ax10 pf

0.033f= x10-6 f
We need to convert 0.1f capacitor to 0.1pf
Means 10-12 which is equal to pf
So we multiply with 10-6 & 10+6
Hence
0.033f = 0.033x10-6 x10-6x10+6f --------[10-6-6=10-12pf]
0.033f =0.033x10+6pf
0.033f =0.033x10+6pf
0.033f =x10-3x10+3x10+3pf
0.033f =x10+3pf-------[10+3=3 like in resistor [no. of zeros]
0.033f =capacitor code)

## Conversion of capacitance from

nf *pf
To

33nf=x10-9 f
We need to convert 33nf capacitor to pf
Means 10-12 which is equal to pf
So we multiply with 10-3 & 10+3 {because -9-3=-12=pf}
Hence
33nf =x10-9 ]x10-3x10+3f [10-9-3=10-12=pf]
33nf =x10-9-3 x10+3f
33nf =x10+3pf
33nf =x10+3pf
33nf =capacitor code)
Hence in general form:

+3

anf=ax10 pf